Um modelo lean & green para a ecoeficiência em processos produtivos da construção civil - Rezende, Marilia de Oliveira (2019)
In Brazil, construction activities are fundamental for economic and social development. However, its importance is damaged by the intensive consumption of natural resources and use of energy. It is estimated that 50% of annual solid waste generated in Brazil comes from the civil construction, but few companies seek to change it. Therefore, it is desirable study ways to add value and reduce the environmental impacts while maintaining business viability of construction activities. Lean Construction (through Lean production) and Sustainable construction issues can solve these questions, but there are few studies that focus on integrated approach of Lean & Green with business perspective. In this sense, this study aims to propose a Lean & Green model for assessment of construction processes using eco-efficiency indicators. The model combined: Value Stream Mapping (VSM), Life Cycle Assessment (LCA) and eco-efficiency indicators, in a cradle-to-handover perspective for seven categories of environmental impacts. The application of the model was done by a case study that considered the concrete frame and light steel framing (LSF) processes of the same high standard residence located in Sorocaba/SP. The results showed that the LSF had higher environmental impacts than concrete alternative in five of the seven evaluated categories. Nevertheless, under the analysis of eco-efficiency indicators, the LSF presented better indicators than concrete frame in four of the seven categories. To guiding decision-makers, the Lean & Green approach considers four possible results for the analysis of the indicators and provides recommendations on how to achieve the scenario of sustainable construction, which increases added value and reduces environmental impacts, maintaining business competitiveness. Finally, compared to other existing Lean & Green models from literature, the proposal of eco-efficiency indicators based on VSM + LCA was a differential of this study, as it brings new guidelines to make construction processes closer to the integrated sustainability needs.